1978
DOI: 10.1002/he.36919782211
|View full text |Cite
|
Sign up to set email alerts
|

Challenging the assumptions of leadership: Women and men of the academy

Abstract: Higher education systems must change to include women administrators because huge pools of creative and effective talent should not be ignored. The increasing complexity of higher education requires the talents of women and men working together.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Leadership development training has been recognized as important to higher education administration advancement (McDade, 1990;Touchton et al, 1993). No gender difference in the reported rate of participation in leadership development programs was found in Hypothesis 5.…”
Section: Professional Assetsmentioning
confidence: 84%
See 4 more Smart Citations
“…Leadership development training has been recognized as important to higher education administration advancement (McDade, 1990;Touchton et al, 1993). No gender difference in the reported rate of participation in leadership development programs was found in Hypothesis 5.…”
Section: Professional Assetsmentioning
confidence: 84%
“…Career planning has been defined as having a goal and a plan for how to achieve that goal. Research has shown that career planning has a positive effect on women's career development and advancement (Hirsch, 1994), as well as on the achievement of high level leadership positions in higher education (LeBlanc, 1993;Touchton et al, 1993). No studies were found comparing the rates or nature of male and female career planning in higher education, which if such differences exist, could impact the disparity in advancement.…”
Section: Career Planningmentioning
confidence: 99%
See 3 more Smart Citations